The use of Bioceramics as root-end filling materials in periradicular surgery: A literature review - Sumaya M. Abusrewil; William McLean; J. Alun Scott (Saudi Dental Journal)
Introduction: Periradicular surgery involves the placement of a root-end filling following root-end resection, to provide an apical seal to the root canal system. Historically several materials have been used in order to achieve this seal. Recently a class of materials known as Bioceramics have been adopted. The aim of this article is to provide a review of the outcomes of periradicular surgery when Bioceramic root-end filling materials are used on human permanent teeth in comparison to “traditional” materials. Methods & results: An electronic literature search was performed in the databases of Web of Science, PubMed and Google Scholar, between 2006 and 2017, to collect clinical studies where Bioceramic materials were utilised as retrograde filling materials, and to compare such materials with traditional materials. In this search, 1 systematic review and 14 clinical studies were identified. Of these, 8 reported the success rates of retrograde Bioceramics, and 6 compared treatment outcomes of mineral trioxide aggregate (MTA) and traditional cements when used as root-end filling materials. Conclusion: Bioceramic root-end filling materials are shown to have success rates of 86.4–95.6% (over 1–5 years). Bioceramics has significantly higher success rates than amalgam, but they were statistically similar to intermediate restorative material (IRM) and Super ethoxybenzoic acid (Super EBA) when used as retrograde filling materials in apical surgery. However, it seems that the high success rates were not solely attributable to the type of the root-end filling materials. The surgical/microsurgical techniques and tooth prognostic factors may significantly affect treatment outcome. Keywords: Calcium silicate cement, Root-end filling, Mineral trioxide aggregate, Microsurgical endodontics, Periradicular surgery